Rancang Bangun Aplikasi Pencatatan Perbaikan Dan Perawatan Perangkat Keras Pada Akademi Sekretari Widya Mandala - Safitri, Neziha Rahma; widodo, arifin puji; susanto, teguh (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Abstract: Recording hardware repair and maintenance at the Academy Secretary Widya Mandala is an application that helps to overcome the existing problems . High utility and never carried out checks on the computer laboratory conditions that often damage . Laboratory has the responsibility to care for and determine the condition of each computer so it does not interfere with the practicum and when the exam .A recording application hardware repair and maintenance needs to be applied to the Academy Secretary Widya Mandala to help resolve problems that occur in the process of monitoring the condition of the computer . This application can schedule repairs by using FIFO which means any damage will get services in advance and use PRIORITY will gain priority value to be done first .With this application, recording hardware repair and maintenance can determine the condition of each laboratory and readiness computer laboratory before being used by the practitioner . The data generated can know how many times the damage and can turn a new computer . Keyword : Damage , Priority , Repair, Fifo .